2018
DOI: 10.1037/men0000100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relationship skills education on pathways of associations between paternal depressive symptoms and IPV and childhood behaviors.

Abstract: The influence of relationship skills education on pathways of associations between paternal depressive symptoms and intimate partner violence and children’s internalizing and externalizing behaviors via paternal warmth and avoidance of destructive conflict behavior was assessed. Participants were 3,045 low-income Hispanic American, European American, and African American fathers from the Building Strong Families Study. Families were drawn from 8 urban and rural areas across the United States and randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The links between destructive conflict, child emotional insecurity, and child behavior problems are consistent with the tenants of EST and EST-R (Davies & Cummings, 1994;Davies & Martin, 2013), as well as findings from prior research (Cummings et al, 2004;Kopystynska et al, 2017;Roopnarine & Dede Yildirim, 2018). More destructive conflict directly predicted increased levels of child behavior problems, as well as indirectly predicted increased levels of child behavior problems via increased levels of child emotional insecurity although the magnitude of the indirect effect was small.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The links between destructive conflict, child emotional insecurity, and child behavior problems are consistent with the tenants of EST and EST-R (Davies & Cummings, 1994;Davies & Martin, 2013), as well as findings from prior research (Cummings et al, 2004;Kopystynska et al, 2017;Roopnarine & Dede Yildirim, 2018). More destructive conflict directly predicted increased levels of child behavior problems, as well as indirectly predicted increased levels of child behavior problems via increased levels of child emotional insecurity although the magnitude of the indirect effect was small.…”
Section: Discussionsupporting
confidence: 81%
“…As alluded to above, the current study also uses data from the BSF project, but it is different from Kopystynska et al (2017) and Roopnarine and Dede Yildirim's (2018) in that we examine mechanisms underlying the links between interparental conflict and child behavior problems via child emotional insecurity. We include child behavior problems as our main outcome because research has shown a direct link between interparental conflict (especially destructive conflict) and child behavior problems (Cummings et al, 2004).…”
Section: Prior Studies Of Interparental Conflict Using the Bsf Data Setmentioning
confidence: 99%
“…Although this measure is similar to measures used in prior studies of paternal warmth (Baker, 2017; Coley et al, 2011; Harper & Fine, 2006), these items do not capture other important dimensions of parental warmth, such as intimate aspects of parental sensitivity, care, and support. The limitation of the parental warmth measure used in BSF is noted in prior research (Roopnarine & Dede Yildirim, 2017). The items show low internal reliability, which is expected given that the measure consists of only three items (Zaslow et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…One previous study of the Building Strong Families (BSF) intervention demonstrated that paternal warmth at 36-months did not mediate the influence of paternal depressive symptoms or interpersonal violence (IPV) on children’s behavioral problems (Roopnarine & Dede Yildirim, 2017). This study focused on interparental conflict, and the results suggested that high levels of paternal warmth do not attenuate the negative relationship of interparental conflict on child behavior problems.…”
Section: The Role Of Maternal Behaviorsmentioning
confidence: 99%
“…The drawbacks of this method of collecting data are well-known and include method-variance issues and reporting bias (Podsakoff, MacKenzie, Lee, & Podsakoff, 2003). It would have also been helpful had we assessed and included the relationship quality between spouses/partners and support networks in our analyses as these family factors have been shown to influence paternal engagement with children and to mediate associations between parenting and childhood outcomes (Roopnarine & Dede Yildirim, 2018).…”
Section: Discussionmentioning
confidence: 99%